Extending DualSPHysics with a Differential Variational Inequality: modeling fluid-mechanism interaction. (July 2018) - Canelas, R.B.; Brito, M.; Feal, O.G.; Domínguez, J.M.; Crespo, A.J.C.
Highlights: A meshless CFD model was coupled to a multi-body solver to reproduce complex flows. The coupled model takes advantage of advanced parallel computing frameworks. A large set of dynamic and kinematic restrictions are available and easy to define. Fluid-mechanism flows are correctly recovered from validation cases. Speculative demonstration cases show the versatility and potential of the model. Abstract: This work details the coupling of a Smoothed Particle Hydrodynamics (SPH) fluid solver with a general-purpose Differential Variational Inequality (DVI) based non-smooth multibody dynamics solver, allowing for efficient and accurate modeling of fluid-mechanism interactions, an ubiquitous scenario in natural and industrial settings. The SPH fluid model (DualSPHysics) can deal with flow non-linearities, free-surface and intense topological changes, while the non-smooth dynamics model (Project Chrono) deals with discontinuous frictional contacts and kinematic restrictions. An open-source integrated framework to model fluid–structure–structure coupled systems is presented by implementing Project Chrono under DualSPHysics. The model is validated with fluid–structure–structure interaction cases. Both frictional and multi-restriction based behaviors are tested and simple convergence analysis are presented, showing that the model is capable of reproducing complex interactions. Several hypothetical cases are then presented, in order to demonstrate possible applications, showcasing a wide set of options useful for practitioners requiring the use of advanced fluid-mechanism models.